Using an RNA aptamer probe for super-resolution imaging of native EGFR. Issue 1 (28th August 2018) - Yan, Qiuyan; Cai, Mingjun; Zhou, Lulu; Xu, Haijiao; Shi, Yan; Sun, Jiayin; Jiang, Junguang; Gao, Jing; Wang, Hongda
Abstract : Using aptamer recognized membrane EGFR with high specificity and improved precision in super-resolution imaging. Abstract : Aptamers, referred to as "chemical antibodies", are short single-stranded oligonucleotides that bind to targets with high affinity and specificity. Compared with antibodies, aptamers can be designed, developed and modified easily. Since their discovery, aptamers have been widely used in in vitro diagnostics and molecular imaging. However, they are relatively less studied and applied in advanced microscopy. Here we used an RNA aptamer in dSTORM imaging and obtained a high-quality image of EGFR nanoscale clusters on live cell membranes. The results showed that the cluster number and size with aptamer labeling were almost the same as those with labeling with the natural ligand EGF, but the morphology of the clusters was smaller and more regular than that with cetuximab labeling. Meanwhile, dual-color imaging demonstrated sufficient fluorophore labeling, highly specific recognition and greatly accurate clustering information provided by aptamers. Furthermore, the aptamer labeling method indicated that active EGFR formed larger clusters containing more molecules than resting EGFR, which was hidden under the antibody labeling. Our work suggested that aptamers can be used as versatile probes in super-resolution imaging with small steric hindrance, opening a new avenue for detailed and precise morphological analysis of membrane proteins.